2019
DOI: 10.1055/s-0038-1676980
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided versus Conventional Caudal Block in Children: A Prospective Randomized Study

Abstract: Background Injection to the accurate area without any complications is the main factor for the efficiencies of caudal block. The aim of this study was to compare success and the complications of conventional and ultrasound method for caudal block in children. Materials and Methods Two-hundred sixty-six American Society of Anesthesiologists (ASA) category 1 children aged between 6 months and 6 years undergoing hypospadias, circumcision, or both surgeries were randomly allocated two groups (Group C o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
11
2
Order By: Relevance
“…In that study, differences were shown in first‐pass success rates and number of total puncture attempts. The nonultrasound ultrasound and ultrasound groups had a first puncture success rate of 66.2% vs 92.5%, respectively, compared to our first‐pass success rate of 46% when heterogenous proceduralists 18 …”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…In that study, differences were shown in first‐pass success rates and number of total puncture attempts. The nonultrasound ultrasound and ultrasound groups had a first puncture success rate of 66.2% vs 92.5%, respectively, compared to our first‐pass success rate of 46% when heterogenous proceduralists 18 …”
Section: Discussioncontrasting
confidence: 52%
“…Echogenic needles were easier to see than nonechogenic needles. We did not have a comparative group of patients who received just real‐time caudal ultrasound‐guidance from the start but Karaca compared real‐time ultrasound‐imaging vs landmark technique (no ultrasound verification) and showed no statistical difference in procedure time when all blocks were performed by the same experienced physician 18 . In that study, differences were shown in first‐pass success rates and number of total puncture attempts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Karaca et al . [ 10 ] in a similar study showed the first puncture success rate of 90.2% with ultrasound guidance and 66.2% with conventional block. In this study single puncture success was 64.2% in the conventional group compared to the ultrasound group 90.56%.…”
Section: Discussionmentioning
confidence: 90%
“…and Karaca et al . [ 9 10 ] showed that there was an only marginal difference in the block performing time between both groups and the difference was not statistically significant. One more difference was in the actual time taken to perform the block is different in the above studies.…”
Section: Discussionmentioning
confidence: 99%